2019
DOI: 10.5194/acp-19-4323-2019
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of the aerosol impact on fog microphysics

Abstract: Abstract. Comprehensive field campaigns dedicated to fog life cycle observation were conducted during the winters of 2010–2013 at the Instrumented Site for Atmospheric Remote Sensing Research (SIRTA) observatory in a suburb of Paris. In order to document their properties, in situ microphysical measurements collected during 23 fog events induced by both radiative cooling and stratus lowering are examined here. They reveal large variability in number, concentration and size of both aerosol background before the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(89 citation statements)
references
References 73 publications
(146 reference statements)
3
82
4
Order By: Relevance
“…In previous studies, Gerber () found in a radiation fog that nongradient turbulent mixing can cause an average shape of supersaturated eddies with a median peak supersaturation of 0.049%. Mazoyer et al () also tried to obtain the supersaturation through aerosol and droplet measurements and derived a critical supersaturation with a median of 0.043% during the winters of 2010–2013 at the SIRTA observatory in the suburb of Paris. The results of our method do not deviate much from these measurements or calculations, and the relative low values can be explained by the heavy pollution in the NCP.…”
Section: Application In a Fog Episodementioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, Gerber () found in a radiation fog that nongradient turbulent mixing can cause an average shape of supersaturated eddies with a median peak supersaturation of 0.049%. Mazoyer et al () also tried to obtain the supersaturation through aerosol and droplet measurements and derived a critical supersaturation with a median of 0.043% during the winters of 2010–2013 at the SIRTA observatory in the suburb of Paris. The results of our method do not deviate much from these measurements or calculations, and the relative low values can be explained by the heavy pollution in the NCP.…”
Section: Application In a Fog Episodementioning
confidence: 99%
“…In previous studies, water vapor supersaturation is often involved in the interaction between aerosols and clouds or fogs (Gerber, ; Herich et al, ; Mazoyer et al, ; Su et al, ). Water droplets form by condensation of water vapor on the aerosol particles.…”
Section: Introductionmentioning
confidence: 99%
“…Asmi et al (2012) found that high NCCN/NC was accompanied with the elevated aerosol hygroscopicity parameter κ during winter when longrange transported polluted continental aerosol commonly occurred. At a given ss, Mazoyer et al (2019) also found the CCN…”
Section: Interactions Between Np Nccn and Ncmentioning
confidence: 85%
“…They pushed the minification of cloud droplet sizes (Rosenfeld et al, 2014a), decreased the ambient supersaturation, enhanced the evaporation of small droplets (Ackerman et al, 2004), and finally caused the cloud events to vanish (Mazoyer et al, 2019).…”
Section: Analysis On Typical Cloud Processesmentioning
confidence: 99%
See 1 more Smart Citation